The effect of flaxseed oil on wound healing of streptozotocin-induced diabetic rabbits : a histopathological, immunohistochemical, gene expression and biophysical study - Jabbar, Omar Abdul (Kulliyyah of Medicine, International Islamic University Malaysia, 2021)
Patients with diabetes are susceptible to develop chronic, nonhealing wounds which cause pain, suffering, and poor quality of life. This, together with high prevalence of delayed wound (15%), increases necessity to find new and more efficient approaches for diabetic wound treatment. Researchers have explored flaxseed oil to expedite in vivo wound healing. Flaxseed oil is known for its anti-inflammatory and antioxidative effects that improve wound healing because the inflammatory process and oxidative damage are implicated in the pathogenesis of diabetic wounds. However, studies utilising flaxseed oil on diabetic animal models are scarce. This study investigates the therapeutic effect of flaxseed oil on wound healing in diabetic animals in 4th, 7th, and 14th day intervals. The study has two phases: the streptozotocin (STZ) diabetes induction phase consisting of 27 male rabbits and the flaxseed oil treatment phase applied to diabetic and nondiabetic animals consisting of 54 male rabbits, in which a full-thickness skin incisional wound (15–17 mm length) were created. They were divided into flaxseed group for diabetic (n=9) and nondiabetic animals (n=9). Positive control (Fucidin cream 2%) group for diabetic (n=9) and nondiabetic animals (n=9), and negative control (nontreated) group for diabetic (n=9) and nondiabetic animals (n=9). The gross wound was monitored using a digital camera and J image software to measure wound length. Flaxseed group diabetic animals group showed regular and approximate smooth edges of the skin wound with organised brightly coloured eschar tissue. All groups have the same days of complete wound closure. However, the wound healing efficiency was higher for flaxseed group diabetic animals (p<0.05) than the control group. The assessment of skin elasticity for flaxseed group nondiabetic animals had the highest viscoelasticity (VE) values with significant differences for three-week intervals. Histological analyses of H&E and Mallory-Trichrome were used to study wound healing. Immunohistochemical evaluations (VEGF and TGF-β) with biochemical analysis (ELISA) of (MMP-2, PDGF-A, and VEGF) protein expression was performed on day 4, day 7, and day 14 of wound healing. The wound healing of the flaxseed group accelerated initially by increasing cellular proliferation (keratinocytes, fibroblast, and endothelial cell) and reducing inflammation via modulation of the protein signalling pathway. In diabetic animals, flaxseed oil enhanced healing by reducing oxidative damage through increased activities of endogenous antioxidants as the flaxseed antioxidant activity was accompanied by up-regulation of pro-fibrotic (TGF-β) gene expression, which triggers fibrogenesis and angiogenesis of wound healing. These mechanisms were more pronounced in flaxseed groups. This study proved that flaxseed oil is a good product for treating diabetic wounds, either alone or combined with biocompatible and biodegradable wound dressing. In conclusion, the results justified that flaxseed oil can be further developed to obtain new and more efficient dressing agent to treat diabetic wounds and other types of skin wounds.